Towards a single European sky - GRUKSHA-COCKAYNE, Yael (Institutional Knowledge at Singapore Management University, 2009)
We describe an integrated decision-making framework and model that we developed to aid EUROCONTROL, the European air traffic management organization, in its vital role of constructing a single unified European sky. Combining multicriteria decision analysis with large-scale optimization methods, such as integer programming and column generation using branch and price, our model facilitates the process by which the numerous European aviation stakeholders evaluate and select technological enhancements to the European air traffic management system. We consider multiple objectives and potential disagreements by stakeholders regarding the impact of proposed system enhancements and allow for different priorities for each key performance area. In an earlier paper, we described the mathematical programming model in detail. In this paper, we elaborate on the broader decision framework and supporting methodologies to help EUROCONTROL in its facilitation role. Using our model and decision framework, EUROCONTROL is currently selecting a set of enhancements to the European aviation system upon which all stakeholders have agreed.